Insight and Violence: An Overview of the Possible Link and Treatment Options in Forensic Psychiatric Settings - Bianca-Mălina Horgoș; Daniel Ungureanu; Cătălina-Angela Crișan (Psychiatry International)
The belief that people suffering from psychiatric disorders are more violent, in particular psychotic patients that do not have insight into their illness, is very common in the general population. Therefore, this review aimed to present a more accurate depiction of the link between lack of insight and violent behavior, by evaluating the existing scientific literature on the topic. For this purpose, a literature search on PubMed, Embase, and Google Scholar was conducted, selecting the relevant papers published during a 20-year period (2004–2024). The paper defined insight as a multi-dimensional concept and discussed its classification, explanatory models, and clinical implications, followed by a presentation of several insight-measuring scales. The meaning of violent behavior, its prevalence, underlying mechanisms, and different measuring scales were discussed, followed by the confounding factors that influence the relationship between insight and violent behavior, treatment options for violence in forensic psychiatry settings, and methods to improve medication adherence. Contrasting results were observed regarding the impact of each factor on leading to violent acts, which suggested that the relationship between insight and violence is more complex than previously thought. In conclusion, increased attention must be paid to the investigated dimensions of both the concepts and the confounding factors, with further research required on this topic.